2023
DOI: 10.1039/d3cy00543g
|View full text |Cite
|
Sign up to set email alerts
|

Surface silanol sites in mesoporous MFI zeolites for catalytic Beckmann rearrangement

Abstract: Silanol groups were generated in siliceous MFI zeolite nanosheets, via alkali-free synthesis routes, for catalytic application for gas-phase Beckmann rearrangement. The catalytic conversion by the zeolite nanosheets was investigated at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Park et al [143] reported the use of silanol groups were generated in siliceous MFI zeolite nanosheets, via alkali-free synthesis routes, for catalytic application for gas-phase Beckmann rearrangement. The catalytic conversion by the zeolite nanosheets was investigated at 310 or 350 °C with cyclohexanone oxime, 4phenylcyclohexanone oxime and cyclododecanone oxime.…”
Section: Beckmann Rearrangmnet In Gas Phasementioning
confidence: 99%
“…Park et al [143] reported the use of silanol groups were generated in siliceous MFI zeolite nanosheets, via alkali-free synthesis routes, for catalytic application for gas-phase Beckmann rearrangement. The catalytic conversion by the zeolite nanosheets was investigated at 310 or 350 °C with cyclohexanone oxime, 4phenylcyclohexanone oxime and cyclododecanone oxime.…”
Section: Beckmann Rearrangmnet In Gas Phasementioning
confidence: 99%
“…Afterward, zeolites with a high Si/Al ratio, especially pure-silicon zeolites with silanol active sites, displayed much better catalytic activity and relative longer lifetime owing to the greater effectiveness of weak acid sites than acidic SiOH­[Al] groups which give rise to reduced activity and consecutive reactions in the vapor-phase process. , Meantime, the main reaction mechanism of the vapor-phase BR process from CHO to CPL over silanols has been revealed, , which proceeds with 1, 2 H-shift, rearrangement, and tautomerization reaction steps. , However, there are some certain amount of side-products, such as 5-hexenenitrile, hexanenitrile, cyclohexanone, and 2-cyclohexen-1-one are generated unexpectedly to make the whole reaction network remains unclear. , Hence, further investigation merits to precisely cut off the corresponding side reactions to improve the CPL selectivity. Then, the effects of various silanols, especially the terminal silanols and silanol nests, were investigated, which point out that silanol nests are more effective to catalyze the vapor-phase BR due to the lower reaction barrier than that of terminal silanols. ,, However, the detailed impacts of terminal silanols are still ambiguous. In addition, introducing mesopores or even macropores into zeolite particles has been proven to be an effective way to promote mass diffusivity, ascribed to the promoted cooperation between reactivity and mass transfer within the confined space.…”
Section: Introductionmentioning
confidence: 99%